(untitled) (Stavební obzor - Civil Engineering Journal, 2017)
This paper describes prestressed steel wire ropes as a way to strengthen a 20-year-old RC T-beam bridge. High strength, low relaxation steel wire ropes with minor radius, high tensile strain and good corrosion resistance were used in this reinforcement. The construction process for strengthening with prestressed steel wire ropes—including wire rope measuring, extruding anchor heads making, anchorage installing, tensioning steel wire ropes and pouring mortar was described. Ultimate bearing capacity of the bridge after strengthening was discussed based on the concrete structure theory. The flexural strength of RC T-beam bridges strengthened with prestressed steel wire ropes was governed by the failure of concrete crushing. To investigate effectiveness of the strengthening method, fielding-load tests were carried out before and after strengthening. The results of concrete strain and deflection show that the flexural strength and stiffness of the strengthened beam are improved. The crack width measurement also indicates that this technique could increase the durability of the bridge. Thus, this strengthened way with prestressed steel wire rope is feasible and effective.